About Friends in the Style of ODE - Dilrabo Quvvatova; Uraeva Darmonoy Saidahmadovna; Sumaira Nawaz (Researchparks Publishing, 2021)
The article is devoted to the analysis of methodological research in modern Uzbek epics. In this regard, the manifestation of the peculiarities of the poem in the epics of M. Shaykhzoda